ACCOUNTING IN PRIVATE ENTERPRISES: PROBLEMS AND PROPOSALS - Alimukhamedova Feruza Mirobitovna (Bright Mind Publishing, 2025)
This paper explores the current state of accounting practices in private enterprises in Uzbekistan, highlighting the key challenges faced by small and medium-sized businesses in organizing accurate and efficient accounting systems. It discusses the discrepancies between theoretical accounting standards and real-world application, particularly in the context of legal, technological, and personnel constraints. The study aims to present actionable suggestions to improve accounting processes in private companies by incorporating digital solutions, training, and regulatory reforms.
Keywords: Private enterprises, accounting system, financial reporting, Uzbekistan, challenges, automation, tax accounting, recommendations, bookkeeping, accounting standards, SMEs, transparency, training, internal control, reforms.